Imaging Insights of Isolated Idiopathic Dystonia: Voxel-Based Morphometry and Activation Likelihood Estimation Studies - Wu, Yunhao; Zhang, Chao; Li, Yufei; Feng, Jie; Zhang, Ming; Li, Hongxia; Wang, Tao; Zhang, Yingying; Jin, Zhijia; Zhang, Chencheng; Zhang, Yuyao; Li, Dianyou; et al. (Frontiers in Neurology, 2022)
The understanding of brain structural abnormalities across different clinic forms of dystonia and their contribution to clinical characteristics remains unclear. Our objective is to investigate shared and specific grey matter volume (GMV) abnormalities in various forms of isolated idiopathic dystonia. We collected imaging data from 73 isolated idiopathic dystonia patients and matched healthy controls to explore the GMV alterations in patients and their correlations with clinical characteristics using voxel-based morphometry (VBM) technique. In addition, we conducted an activation likelihood estimation (ALE) meta-analysis of previous VBM studies. Our study demonstrated wide-spread morphometry alterations in patients with idiopathic dystonia. Multiple systems were affected, which mainly included basal ganglia, sensorimotor, executive control, and visual networks. As the result of ALE meta-analysis, convergent cluster with increased GMV was found in the left globus pallidus. In subgroup VBM analyses, decreased putamen GMV was observed in all clinic forms, while the increased GMV was observed in parahippocampal, lingual, and temporal gyrus. GD demonstrated the most extensive GMV abnormalities in cortical regions, and the aberrant GMV of posterior cerebellar lobe was prominent in CD. Moreover, trends of increased GMV regions of left precuneus and right superior frontal gyrus were demonstrated in the moderate-outcome group compared to superior-outcome group. Results of our study indicated a shared pathophysiology of the disease centered on the dysfunction of basal ganglia-thalamo-cortical circuit, impairing sensorimotor integration, high-level motor execution and cognition of patients. Dysfunction of cerebello-thalamo-cortical circuit could also be involved in CD especially. Finally, the frontal-parietal pathway may act as a potential marker for predicting treatment outcomes such as deep brain stimulation.